Reputation
Next privilege 20 Rep.
Talk in chat
 Sep24 awarded Autobiographer Jan13 awarded Commentator Oct18 accepted How do I show the Wronskian of $(J_{a}(x),Y_{a}(x)) = \dfrac {2} {\pi x}$ Oct16 comment How do I show the Wronskian of $(J_{a}(x),Y_{a}(x)) = \dfrac {2} {\pi x}$ What do you mean by that? Oct16 asked How do I show the Wronskian of $(J_{a}(x),Y_{a}(x)) = \dfrac {2} {\pi x}$ Oct16 accepted How can I get $B(x,y+1)= \frac{y}{x+y} B(x,y)$ using integration by parts? Oct16 accepted How to find $\lim_{x \rightarrow -N} J_{a} = (-1)^N J_{N}$? Oct8 revised How to find $\lim_{x \rightarrow -N} J_{a} = (-1)^N J_{N}$? edited title Oct7 comment How to find $\lim_{x \rightarrow -N} J_{a} = (-1)^N J_{N}$? I don't understand how you get the last step in your final result. How does -N become +N ? I initially though you added k+N whenever there was k, but then I noticed that didn't work. Thanks! Oct7 revised How can I get $B(x,y+1)= \frac{y}{x+y} B(x,y)$ using integration by parts? fixed grammar Oct7 asked How can I get $B(x,y+1)= \frac{y}{x+y} B(x,y)$ using integration by parts? Oct7 asked How to find $\lim_{x \rightarrow -N} J_{a} = (-1)^N J_{N}$? Oct7 awarded Scholar Oct7 accepted How to show $\lim_{x \to -N} (x+N) \Gamma(x)$ =$(-1)^N/N!$? Oct7 comment How to show $\lim_{x \to -N} (x+N) \Gamma(x)$ =$(-1)^N/N!$? Using some of these ideas, and trying to formulate my own answer based off of what I actually know, I got $lim_{x \rightarrow -N} (x+N) \Gamma(x)$ = $lim_{x \rightarrow -N} (x+N) \frac{\Gamma(x+N)}{(x)_{N}}$ = $lim_{x \rightarrow -N} \frac {\Gamma(x+N+1)}{x(x+1)(x+2)...(x+N+1)}$ =$\frac{\Gamma(1)}{(-1)[N(N-1)(N-2)...1]}$ =$\frac{1}{(-1)(N!)}$ which is still wrong I think. Oct7 revised How to show $\lim_{x \to -N} (x+N) \Gamma(x)$ =$(-1)^N/N!$? corrected spelling Oct7 comment How to show $\lim_{x \to -N} (x+N) \Gamma(x)$ =$(-1)^N/N!$? I can follow your work easiest since this formula is in my reference sheet. I don't understand the purpose of making the y = x+n substitution. Is it necessary? Can it be done without it? For $\Gamma (1+n-y)$ it disappeared from your second line when you transitioned to the third line to $\Gamma (1+n)$. Wasn't the $sin(\pi y - \pi n) = (-1)^n sin(\pi y)$ in the denominator? How did the $(-1)^n$ get moved to the numerator? Oct7 awarded Student Oct7 comment How to show $\lim_{x \to -N} (x+N) \Gamma(x)$ =$(-1)^N/N!$? Thanks I will look into it. I am taking an undergraduate course in differential equations and we are using the gamma function for bessel ODE and we are using this notation. So I know nothing of the terminology that you used. I just have a sheet with gamma properties. Oct7 asked How to show $\lim_{x \to -N} (x+N) \Gamma(x)$ =$(-1)^N/N!$?